Attenuation of scopolamine-induced learning deficits by LVV-hemorphin-7 in rats in the passive avoidance and water maze paradigms - Albiston, Anthony L; Pederson, Eric S; Burns, Peta; Purcell, Brett; Wright, John W; Harding, Joseph W; Mendelsohn, Frederick A; Weisinger, Richard S; Chai, Siew Yeen (Behavioural brain research, 2004)
Central administration of angiotensin IV (Ang IV) analogues attenuates scopolamine-induced amnesia. Ang IV mediates its effects by binding to a high affinity, binding site, AT 4 receptor, that has recently been identified as insulin regulated aminopeptidase (IRAP). The purpose of this study was to examine the effect of the distinct AT 4 ligand, LVV-hemorphin-7 (LVV-H7), on scopolamine-induced learning deficits, one which involves fear-conditioning and the other spatial learning. Rats were pretreated with an intracerebroventricular (ICV) dose of scopolamine hydrobromide followed by treatment with 1 nmol LVV-H7 or artificial cerebrospinal fluid (aCSF). During the acquisition phase of the water maze task, daily ICV infusions of 1 nmol of LVV-H7 25 min after scopolamine treatment produced marked improvement in both the latency and distance swum in order to locate the submerged platform using visual cues compared to animals treated with scopolamine only. In addition, the same dose of LVV-H7 attenuated the learning deficit observed for scopolamine-treated animals in the passive avoidance task. These studies clearly demonstrate that LVV-H7, like Ang IV, is a pharmacologically active AT 4 ligand that attenuates the deleterious effects of scopolamine on learning performance in two different behavioral paradigms.